2018
DOI: 10.1039/c8nj04802a
|View full text |Cite
|
Sign up to set email alerts
|

A pillar[5]arene-calix[4]pyrrole enantioselective receptor for mandelate anion recognition

Abstract: A novel pillar[5]arene-calix[4]pyrrole was synthesized as a chiral receptor for mandelate anions with a maximum enantioselectivity of 2.47.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Compared with molecular chirality, the supramolecular chirality is more attractive in terms of their regulatability by the external conditions such as temperature ( Yao et al, 2017 ; Fan et al, 2019 ), pH ( Kanagaraj et al, 2020 ; Liang et al, 2020 ; Hao et al, 2021 ), redox ( Xiao et al, 2020 ), light ( De Poli et al, 2016 ), chemical additives ( Lee et al, 2018 ), pressure ( Yao et al, 2021a ), and solvents ( Borovkov et al, 2003b ; Fan et al, 2019 ). Pillar[n]arenes ( Ogoshi et al, 2008 ; Xue et al, 2012 ; Pan et al, 2015 ; Fan et al, 2016 ; Jie et al, 2018 ; Lv et al, 2018 ; Li G. et al, 2019 ; Xiao et al, 2019 ; Ji et al, 2020a ; Lou and Yang, 2020 ; Mi et al, 2020 ; Liu et al, 2021 ; Peng et al, 2021 ), as a relatively new class of synthetic macrocyclic hosts with some unique properties ( Guo et al, (2018) ; Lai et al, (2019) ; Liu et al, (2019) ; Wang et al, (2021 ), have proved to be an ideal platform to construct unimolecular chirality based on different external stimuli-driven. We have demonstrated that the chirality of pillar[n]arene derivatives could be manipulated by external stimuli, including temperature, redox, light, and pressure ( Yao et al, 2017 ; Xiao et al, 2020 ; Yao et al, 2021a ; Yao et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with molecular chirality, the supramolecular chirality is more attractive in terms of their regulatability by the external conditions such as temperature ( Yao et al, 2017 ; Fan et al, 2019 ), pH ( Kanagaraj et al, 2020 ; Liang et al, 2020 ; Hao et al, 2021 ), redox ( Xiao et al, 2020 ), light ( De Poli et al, 2016 ), chemical additives ( Lee et al, 2018 ), pressure ( Yao et al, 2021a ), and solvents ( Borovkov et al, 2003b ; Fan et al, 2019 ). Pillar[n]arenes ( Ogoshi et al, 2008 ; Xue et al, 2012 ; Pan et al, 2015 ; Fan et al, 2016 ; Jie et al, 2018 ; Lv et al, 2018 ; Li G. et al, 2019 ; Xiao et al, 2019 ; Ji et al, 2020a ; Lou and Yang, 2020 ; Mi et al, 2020 ; Liu et al, 2021 ; Peng et al, 2021 ), as a relatively new class of synthetic macrocyclic hosts with some unique properties ( Guo et al, (2018) ; Lai et al, (2019) ; Liu et al, (2019) ; Wang et al, (2021 ), have proved to be an ideal platform to construct unimolecular chirality based on different external stimuli-driven. We have demonstrated that the chirality of pillar[n]arene derivatives could be manipulated by external stimuli, including temperature, redox, light, and pressure ( Yao et al, 2017 ; Xiao et al, 2020 ; Yao et al, 2021a ; Yao et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…As a highly investigated anion receptor system, the calix[4]pyrrole scaffold was modified to provide enantioselectivity. Aromatic extension to produce pillar[5]arene‐calix[4]pyrrol receptors were found to differentiate between the stereoisomers of mandelate with a selectivity up 2.47 in DMSO [12a] and aliphatically extended calix[4]arene receptors with a selectivity up to 3.5 in DMSO [12d] . As a chiral director, substantial research efforts have been devoted towards the incorporating the bisbinaphthyl moiety into anion receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Upon utilizing these concepts, the enantioselective binding of mandelate has been previously reported. [12] The majority of chiral receptors display limited anion affinity and enantioselectivity, thus, opportunities remain to develop novel chiral receptor motifs.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of macrocyclic compounds have been developed for the purpose of studying their optical properties [10][11][12]. Recently, the chirality of a novel emerging host molecule, pillar[n]arenes, has attracted increasing attention [13][14][15][16]. Pillar[n]arenes are macrocyclic compounds that are composed of several hydroquinone ether units and are featured by the well-defined cavity, unique host-guest complexation properties, and readily chemical functionalization.…”
Section: Introductionmentioning
confidence: 99%